Thermochronology of the Sulu ultrahigh-pressure metamorphic terrane: Implications for continental collision and lithospheric thinning - Liu, L.; Li, Zheng-Xiang; Danisik, Martin; Li, S.; Evans, Noreen; Jourdan, Fred; Tao, N. (Elsevier BV, 2017)
The thermal history of the Dabie-Sulu orogenic belt provides important constraints on the collision process between the South China and North China blocks during the Mesozoic, and possible lithospheric thinning event(s) in the eastern North China Block. This study reports on the thermal evolution of the Sulu ultrahigh-pressure metamorphic (UHP) terrane using zircon U-Pb geochronology and multiple thermochronology methods such as mica and hornblende 40Ar/39Ar, zircon and apatite fission track, and zircon and apatite (U-Th)/He dating. 40Ar/39Ar and zircon (U-Th)/He data show that the UHP terrane experienced accelerated cooling during 180–160 Ma. This cooling event could be interpreted to have resulted from extensional unroofing of an earlier southward thrusting nappe, or, more likely, an episode of northward thrusting of the UHP rocks as a hanging wall. A subsequent episode of exhumation took place between ca. 125 Ma and 90 Ma as recorded by zircon (U-Th)/He data. This event was more pronounced in the northwest section of the UHP terrane, whereas in the southeast section, the zircon (U-Th)/He system retained Jurassic cooling ages of ca. 180–160 Ma. The mid-Cretaceous episode of exhumation is interpreted to have resulted from crustal extension due to the removal of thickened, enriched mantle. A younger episode of exhumation was recorded by apatite fission track and apatite (U-Th)/He ages at ca. 65–40 Ma. Both latter events were linked to episodic thinning of lithosphere along the Sulu UHP terrane in an extensional environment, likely caused by the roll-back of the Western Pacific subduction system.